دور برنامج (نور) للإدارة الإلكترونية في تحسين أداء العاملين بمكتب تعليم البنات بمحافظة الأسياح في منطقة القصيم بالمملكة العربية السعودية - F. Alfuhaid, S.A.; Yussuf, A.; Tengku Kasim, T.S.A. (Universiti Sains Islam Malaysia, 2024)
As a result of the rapid developments and changes at the educational institutions, the responsibility of the management personnel has become greater; to ensure that these institutions remain in line with rapid developments and changes, to increase their competitiveness and excellence in the era of modern knowledge and technology. Therefore, this study aims at diagnosing the contribution of the electronic management program Noor in improving the staff performance at the Girls' Education Office in the Governorate of Asayah. The researcher adopted quantitative approaches; A questionnaire consisting of (30) items within four areas was used as a basic data collection tool, these data were enhanced through the interview. The researcher chose a random sample of 25 individuals at the study community, consisting of: (5) heads of departments, (6) administrators and (14) principals and their assistance; who perform their work using Noor Electronic Management System. The findings revealed that the contribution of Noor electronic management program' in improving the administrative performance at the Girls' Education Office in Al-Asayah Governorate at Al-Qassim region in both fields of student affairs administration and the management of teachers affairs were high.